2002
DOI: 10.4269/ajtmh.2002.66.745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two enzyme-linked immunosorbent assay methods for detection of immunoglobulin M antibodies in acute leptospirosis.

Abstract: Abstract. Leptospirosis is a common zoonosis of worldwide distribution. Diagnosis of leptospirosis is usually accomplished by serology, but the microscopic agglutination test (MAT) generally requires paired sera for detection of seroconversion and is considered too complex for routine use. A number of rapid assays have been developed in recent years. In the present study, 2 immunoglobulin (Ig) M enzyme-linked immunosorbent assay (ELISA) methods were evaluated for the early diagnosis of acute leptospirosis in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 26 publications
4
33
0
10
Order By: Relevance
“…Previous studies have consistently shown ELISA to be more sensitive than MAT in the acute phase. 36 Sensitivity of MAT, even with properly obtained paired samples, is not 100% as specified in several other studies. 10 We observed similar results in the 2008 Sri Lanka leptospirosis outbreak, with two additional patients detected only using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently shown ELISA to be more sensitive than MAT in the acute phase. 36 Sensitivity of MAT, even with properly obtained paired samples, is not 100% as specified in several other studies. 10 We observed similar results in the 2008 Sri Lanka leptospirosis outbreak, with two additional patients detected only using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Serum polymerase chain reaction or blood culture can provide a definitive diagnosis, 12 but are not widely available. Tests for the presence of genus-specific IgM, 13 which develops within the first week of infection and persists for months, 14 may be used for screening, and a microscopic agglutination test (MAT) can provide greater specificity along with some indication of the infecting serovar. 15 Leptospirosis has been described in several regions of India, [16][17][18][19] but data on the epidemiology of leptospirosis in Bangladesh are limited.…”
mentioning
confidence: 99%
“…Briefly, the wells of polystyrene plates (Nunc) were coated with 100 µl of antigens (10 9 Leptospira boiled in carbonate buffer, 0.1 M, pH 9.6) [19]. The plate was washed three times with 0.1 M PBS containing 0.05% Tween 20 ( PBST) and then blocked with 200 µl/well of 1% BSA for 2 h at room temperature.…”
Section: Evaluation Of Antibody Response By Elisamentioning
confidence: 99%